EKSISTENSI PEMERINTAH KABUPATEN MENJAGA NILAI PENDIDIKAN ISLAM DENGAN MENGUATKAN KEBUDAYAAN DI MANDAILING NATAL - Kasman; Rohman (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2021)
The implementation of Islamic education is not as simple as reversing palm of hand, moreover, the variety of values also affect to the social norm in the era of information technology now. New cultures that comes from external was unable to restrain, it is caused alot of information that easy to find in whole area. So that it touchs the norm of our life in society. This study aims to know the role of the government of Mandailing Natal in maintaining the values of Islamic education in this challenging era. The methode of this study uses qualitative research. That collecting data three steps, that are interview, observation, and documentation study. Furthermore, in analyzing data the researcher also use some steps, namely; data collecting, data display, data reduction, the last conclusion. The result of this study found that the government of Mandailing Natal strives to keep the norms of Islamic education by toughing culture, and tradition. Those are seen in some ways; cultural character education through tradition education; the training of culture and art of Mandailing that developing Islamic nature; tahfidz alquran building; local cultur tourism in Islamic verse.